Traffic Waiting Time Optimization: An Effective Effort to Overcome Congestion at Gede Ngurah Cakranegara Intersection - Setiawati, Setiawati; Rahmi, Dhea Wasila; Syauqi, Shofiyurrahman; Purnamasari, Dara (Semeton Mathematics Journal, 2024)
Intersections are places that are prone to traffic congestion. This is due to the location and function of the intersection, which if left unchecked will lead to accidents. To overcome this problem, traffic lights are made to regulate traffic flow conditions. Gede Ngurah Cakranegara Intersection is an intersection that has high congestion conditions, this is due to its location in the city center and its function as a main road. In addition, the trigger for congestion at the Gede Ngurah Cakranegara intersection is the waiting time which is still not optimal and the lack of orderly drivers in obeying the traffic lights. Thus, the purpose of this study is to optimize the total waiting time at the Gede Ngurah Cakranegara intersection. Total waiting time optimization is done using compatible graph. The compatible graph in this case will describe the condition of traffic flows that will run simultaneously without interfering with each other, so that they are safe and do not collide with each other. This study uses primary data obtained from field observations conducted in the morning, afternoon and evening. After optimization, the total waiting time at the Gede Ngurah Cakranegara intersection following the light signal is 180 seconds and the total waiting time for those who do not follow the light signal is 120 seconds. Compared to the previous waiting time of 538 seconds, a more optimal time was obtained.